MALNUTRISI PADA ANAK USIA DINI - Aditia Saputra; Zimy Steven; Renaldi Renaldi; Iwan Hottua Sihotang; Romiaty Romiaty (CV. ADIBA AISHA AMIRA, 2025)
Malnutrition in early childhood is a global health problem that has a wide impact on physical growth, cognitive development, and the immune system of children. Children with poor nutritional status tend to experience growth retardation, are susceptible to infectious diseases, and experience impaired brain development that can affect intelligence. This study aims to examine the factors causing malnutrition in early childhood, the impacts caused, and solutions that can be applied. This study uses a literature review method by reviewing various scientific journals that discuss malnutrition in early childhood. The study results indicate that malnutrition is caused by factors such as low nutritional intake, family socio-economic conditions, lack of parental education about healthy eating patterns, and limited access to health services. The impacts of malnutrition include impaired growth, decreased immune system, and impaired cognitive development that can have long-term impacts on children's productivity in the future. Solutions that can be done to overcome this problem include educating parents, increasing access to nutritious food, and implamanting more comprehensive health policy interventions. With the right intervention, the rate of malnutrition in early childhood can be reduced so that their quality of life can improve.